If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3x + -10) = 46 Reorder the terms: 6(-10 + 3x) = 46 (-10 * 6 + 3x * 6) = 46 (-60 + 18x) = 46 Solving -60 + 18x = 46 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 18x = 46 + 60 Combine like terms: -60 + 60 = 0 0 + 18x = 46 + 60 18x = 46 + 60 Combine like terms: 46 + 60 = 106 18x = 106 Divide each side by '18'. x = 5.888888889 Simplifying x = 5.888888889
| 5(3x-10)=46 | | 4(3x-10)=46 | | 3(3x-10)=46 | | 1(3x-10)=46 | | 12x-25=-63+7x | | 3(-2x+5)=12-4x | | -8x+4=-2(4x-2) | | -y=12-6x | | -20=2y-4 | | monkey+hat=toad | | 6x-y=12fory | | 8x+4=-2(4x-2) | | G=(x+y)(ax+bxy) | | ln(4-x)+ln(2)=2ln(x) | | G=ax(x+y)+bxy(x+y) | | 5w+10=5w+10 | | -19x-34=56+x | | 25-5x=4x-20 | | 16x-19=120+6x | | 10x+8x+12x+4x+9x+3-12-9+2-3=360 | | 3x+4=9+x | | 2x+9=3x-20 | | 11x+16=3x+13 | | 3(x+12)=9x-14 | | 4(3x-1)=8(x+9) | | 2(x+20)=7x+150 | | -0.333b=9 | | x=5andx-5 | | 5x=-15+5y | | 5(1-7r)=25 | | 23=2+7(z+6) | | x=70-2.5y |